Camille Saint-Saëns and His World - Pasler, Jann (The Bard Music Festival Ser., 2012)
Camille Saint-Saëns--perhaps the foremost French musical figure of the late nineteenth century and a composer who wrote in nearly every musical genre, from opera and the symphony to film music--is now being rediscovered after a century of modernism overshadowed his earlier importance. In a wide-ranging and trenchant series of essays, articles, and documents, Camille Saint-Saëns and His World deconstructs the multiple realities behind the man and his music. Topics range from intimate glimpses of the private and playful Saint-Saëns, to the composer's interest in astronomy and republican politics, his performances of Mozart and Rameau over eight decades, and his extensive travels around the world. This collection also analyzes the role he played in various musical societies and his complicated relationship with such composers as Liszt, Massenet, Wagner, and Ravel. Featuring the best contemporary scholarship on this crucial, formative period in French music, Camille Saint-Saëns and His World restores the composer to his vital role as innovator and curator of Western music [Publisher description].